2022
DOI: 10.3389/fimmu.2022.968686
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy activation by dietary piceatannol enhances the efficacy of immunogenic chemotherapy

Abstract: Immunogenic cell death (ICD) promotes the immune antitumor response via releasing damage-associated molecular patterns (DAMPs) from dying tumor cells. The induction of autophagy improves the efficacy of multiple immunogenic chemotherapies. Here, we show that piceatannol, a dietary phenolic compound that is widely distributed in multiple fruits and vegetables such as grapes, blueberries, and mushrooms, induces autophagy and enhances oxaliplatin (OXA)-induced anticancer immune response. Specifically, piceatannol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…qPCR and western blotting were conducted according to previous protocols [ [30] , [31] , [32] ], and primers for PCR are listed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…qPCR and western blotting were conducted according to previous protocols [ [30] , [31] , [32] ], and primers for PCR are listed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…It is mainly found in grapes, sugar cane, white tea, rhubarb, passion fruit and blueberries (186). Piceatannol is considered to have anticancer, anti-atherogenic, antioxidative, anti-inflammatory, anti-microbial and estrogenic activities, and is widely used in the treatment of heart disease, leukemia and cancer (187)(188)(189)(190). Yao et al found that piceatannol can inhibit apoptosis, inflammation and oxidative stress of podocytes under HG condition.…”
Section: Phenolicsmentioning
confidence: 99%
“…7 In their letter to the editor, Yang et al propose that pharmacological enhancement in the autophagy process can be effective in boosting anticancer immune responses to ICD drugs. 8,9 They propose that ginsenoside Rh2 (G-Rh2) heightened the mitoxantrone (MTX)-induced ICD including adenosine triphosphate (ATP) release increase, discharge of high mobility group box 1 (HMGB1) and repositioning of calreticulin (CALR) to the membrane enhancing anti-tumour immune responses (Figure 1). G-Rh2 are ginsenosides, the main components from ginseng and proved to have pharmacological anti-cancer capabilities, inducing autophagy by activating transcriptional factors…”
mentioning
confidence: 99%